Depressive Symptoms Following Later-life Marital Dissolution and Subsequent Repartnering. (June 2019) - Lin, I-Fen; Brown, Susan L.; Wright, Matthew R.; Hammersmith, Anna M.
The doubling of the divorce rate among individuals over age 50 during the past 20 years underscores the urgency of studying the consequences of gray divorce and subsequent repartnering for adult well-being. We filled this gap by using the 1998-to-2014 Health and Retirement Study to evaluate how the levels of depressive symptoms changed following gray divorce versus widowhood. Individuals who divorced or became widowed already had experienced higher levels of depressive symptoms before dissolution relative to those who remained married. Compared with those who became widowed, those who transitioned to divorce experienced a lower elevation and a shorter time to recovery in depressive symptoms. When repartnering, both groups experienced similar magnitudes of initial reduction and subsequent rates of increase. Both the negative consequences of marital dissolution and the beneficial effects of repartnership for mental health persisted for several years, although ultimately they reverted to their predissolution levels of depressive symptoms.